2016
DOI: 10.1590/s1806-92902016000200004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymer coated slow-release urea on ruminal fermentation and nutrient total tract digestion of beef steers

Abstract: -The objective of this study was to evaluate the effects of polymer coated slow-release urea (SRU) in high-forage diets of beef steers on nutrient intake and digestibility, ruminal fermentation, microbial protein synthesis, and energy balance. Eight 24-mo-old rumen-fistulated castrated Nellore steers (average body weight = 418.0±40.0 kg) were used in a replicated 4 × 4 Latin square design. Animals were randomly distributed to receive one of the following diets: no urea inclusion; 1.0% inclusion of feed grade u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Sulphur supplements can enhance the nutrient digestibility because the synthesis of amino acids that contain sulphur is critical for microbial growth [2627]. Nevertheless, we did not detect differences on microbial protein synthesis agreeing with [28] who reported no differences in purine derivatives production of Nellore steers fed the urea sources of the current study. In addition, Calomeni et al [9] found no differences in DM intake, apparent digestibility and microbial protein synthesis of dairy cows fed the same polymer-coated SRA as used in this study or feed grade urea, but the authors added 0.9 g/kg DM of the commercial products.…”
Section: Discussionsupporting
confidence: 89%
“…Sulphur supplements can enhance the nutrient digestibility because the synthesis of amino acids that contain sulphur is critical for microbial growth [2627]. Nevertheless, we did not detect differences on microbial protein synthesis agreeing with [28] who reported no differences in purine derivatives production of Nellore steers fed the urea sources of the current study. In addition, Calomeni et al [9] found no differences in DM intake, apparent digestibility and microbial protein synthesis of dairy cows fed the same polymer-coated SRA as used in this study or feed grade urea, but the authors added 0.9 g/kg DM of the commercial products.…”
Section: Discussionsupporting
confidence: 89%
“…However, as discussed earlier, tCNSL may not have influenced the responses of the variables in Table 4 due to the characteristic of its composition since it did not present significant amounts of anacardic acid, which is the antimicrobial agent responsible for altering the ruminal microflora and, consequently, the verified answers. Taylor-Edwards et al (2009) and Gardinal et al (2016) evaluated the effect of urea and SRU on the digesta of steers fed a diet with approximately 40% NDF and verified that NPN sources did not influence rumen pH values, being close to 6.5 and 6.42, respectively. However, the animals that fed SRU had lower N-NH 3 concentrations in the rumen fluid in both cases when compared to the use of urea.…”
Section: Itemsmentioning
confidence: 93%
“…The optimal N-NH 3 level varies according to the feed and availability of fermentable carbohydrates in the rumen. However, it is expected that the availability of N-NH 3 from NPN sources may be more limiting for animals with high ruminal N requirements, such as those with a high intake or production demands or those that consume highly degradable feeds when compared to animals that require less N ruminal Hours after 1 st meal Taylor-Edwards et al (2009) and Gardinal et al (2016) evaluated the effect of urea and SRU on the digesta of steers fed a diet with approximately 40% NDF and verified that NPN sources did not influence rumen pH values, being close to 6.5 and 6.42, respectively. However, the animals that fed SRU had lower N-NH 3 concentrations in the rumen fluid in both cases when compared to the use of urea.…”
Section: Itemsmentioning
confidence: 99%
“…Additionally, no change in the total VFA or VFA proportions were reported using urea compared to the SRU. Researchers observed comparable urea effects and recommended that greater acetate and lower butyrate concentrations in diets containing urea produced a lower acetate transformation in conformity with ruminal butyrate (Gardinal et al, 2016;Xin et al, 2010). Khattab, Salem, Abdel-Wahed, &and Kewan (2013) observed greater acetate concentration after feeding urea, and an expansion in microbial protein synthesis.…”
Section: Volatile Fatty Acidsmentioning
confidence: 98%